The Phenomenon of Legal Pluralism at the International Level - اليوسف مضر; ماهر ملندي; موسى خليل متري (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The formation of international legal rules is no longer limited to certain specific sources. Insteadly, new innovative methods have emerged other than traditional international law, and the international scene has become clearly pluralistic, characterized by the diversity of sources from which law is generated, and the conflict of legal rules to regulate the same field. This research aims to study the so-called phenomenon of “legal pluralism” at the international level. To serve this purpose, it seeks to trace its impact, reveal its existence, and demonstrate its importance in forming new rules at the level of international law that are different from the well-known classical rules. The research reveales that legal pluralism is a phenomenon that actually exists at the international level, Then it recommends taking the necessary measures to make legal pluralism more reliable, emphizing the importance of giving it further study and attention in order to have a deeper understanding of how international rules are formed.